Comparative Hematological Profile of Three Species of Schizothorax Group Found in the Streams of Himalayan Region - U, Siddiqui; A, Rani; H.C.S, Bisht; N.N, Pandey (Asian Journal of Biological and Life Sciences)
Assessing hematological parameters offers a comprehensive evaluation of the health condition of fish. The present study evaluated the variations in hematological parameters, including Total Erythrocyte Count (TEC), Total Leukocyte Count (TLC), Hemoglobin (Hb), Hematocrit (Hct), Mean Corpuscular Volume (MCV), Mean Corpuscular Hemoglobin (MCH), and Mean Corpuscular Hemoglobin Concentration (MCHC), in three species of Schizothorax fish (S. richardsonii, S. plagiostomus, and S. progastus). The hematocrict values of the three species differed significantly (S. richardsonii 25.5±2.3 has the lowest hematocrit value compared to S. progastus 27.5±2.6 and S. plagiostomus 29±4.6). S. plagiostomus had considerably greater Hemoglobin (Hb) and Red Blood Cell count (RBC) levels compared to S. richardsonii and S. progastus. The results revealed significant (p<0.05) variations among the three species. The MCHC value ranged between 34.1%, 35.0%, and 35.9% indicating an insignificant (p>0.05) difference. Therefore, the baseline data produced during this study can be efficiently utilised to monitor the health condition of coldwater fishes in order to preserve them sustainably in aquatic systems under the scenario of climate change.
Keywords: Coldwater fishes; Health status Hematological parameters; S. plagiostomus; S. progastus; S. richardsonii